Revolutionizing Plastic Furniture Design: Harnessing the Power of Artificial Intelligence - العوضي، أحمد محمد ناصر; يوسف، ديانا محمد كامل (المؤسسة العربية لإدارة المعرفة, 2023)
شهدت صناعة الأثاث العالمية طفرة في الإقبال على مواد بديلة مثل البلاستيك نتيجة لمرونتها وتكلفتها وفعاليتها، وبالرغم من الطلب المتزايد يواجه تصميم الأثاث البلاستيكي تحديات فريدة تتطلب تصاميم مبتكرة لضمان الوظائف والجمالية والمتانة، يظهر لنا الذكاء الاصطناعي (AI) كأداة واعدة لإعادة تعريف تصميم الأثاث البلاستيكي من خلال تعزيز الإبداع والخبرة البشرية حيث حققت التطورات الأخيرة في الذكاء الاصطناعي تقدما في القدرة على إنشاء تصاميم مفصلة وواقعية، مما يمكن من التصور السريع باستخدام لغة التخاطب الطبيعية، تقدم لنا منصات الذكاء الاصطناعي مثل MidJourney بديلا مثيرا لممارسات التصميم التقليدية وتوفر فرصا لإبداع وإنشاء أثاث مبتكر، على الرغم من البحوث الواسعة في مجالات الذكاء الاصطناعي مثل الهندسة المعمارية وتصميم المنتجات والأزياء إلا أن البحوث المتعلق بتصميم الأثاث باستخدام الذكاء الاصطناعي محدودة، يستكشف هذا البحث MidJourney كأداة تجريبية لتصميم أنماط مختلفة من الأثاث البلاستيكي مسلطا الضوء على التوازن الدقيق بين الجمالية والوظائف وتكنولوجيا التصنيع، تؤكد النتائج التي توصلت لها هذه الدراسة والبيانات المستندة من إفادات الخبراء التي تم جمعها من خلال استبيان عبر الإنترنت فعالية الذكاء الاصطناعي في تصميم الأثاث البلاستيكي وتسليط الضوء على الفوائد العديدة لتقنية الذكاء الاصطناعي في صناعة تصميم الأثاث. The global furniture industry has experienced a surge in demand for alternative materials like plastic, driven by its versatility, cost, and effectiveness. However, designing plastic furniture poses unique challenges that require innovative approaches to ensure functionality, aesthetics, and durability. Artificial intelligence (AI) emerges as a promising tool to redefine plastic furniture design by augmenting human creativity and expertise. Recent advancements in generative AI have revolutionized the ability to generate detailed and realistic representations of design concepts, enabling quick conceptualization using natural language. AI platforms like MidJourney offer an exciting alternative to traditional design practices, providing avenues for innovative and customizable furniture creations. Despite extensive AI research in domains such as architecture, product design, and fashion, minimal research has focused on AI in furniture design. This paper explores MidJourney as an experimental tool for designing various styles of plastic furniture, highlighting the delicate balance between aesthetics, functionality, and manufacturing technology. The generated results from this experimental study and expert feedback from data gathered by an online questionnaire confirms the effectiveness of AI in plastic furniture design based on and emphasizes the numerous benefits of AI technology in the furniture design industry.
Keywords: صناعة الأثاث -- الأثاث البلاستيكي -- الذكاء الاصطناعي -- التصميم الداخلي